Legislation and electronic records management in the Thai Public Sector: Challenges and opportunities in the digital age - Seelakate, Pimphot (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: The Thai public sector requires a legal infrastructure to set the legislative framework governing records and archives management in the Digital Age. Purpose: This research examines Thailand’s current legislation on records and archives management, highlighting its role in addressing issues and gaps in e-records management in the Digital Age. Method: This research follows a qualitative approach, with the purpose of this methodology to gather insights into the legal framework surrounding electronic records management within the Thai public sector. Findings: The results highlight four key issues: 1) the legislation defines different key terms related to information, records, and archives, providing an overlapped framework, 2) It still needs further code of practice for e-records management, 3) the lack of comprehensive guidelines or procedures for records and archives management creates a gap to help standardize and improve records management practices across the public sector, and 4) the effectiveness of legal enforcement is hindered by a lack of public awareness and understanding of records management laws. Conclusion: This research is pioneering in that it addresses electronic records management in the Thai public sector from a records-and-archives management perspective. The findings have the potential to contribute to improving the regulatory framework that governs e-records management in government agencies. This, in turn, will help ensure the preservation of electronic records for future generations in the Digital Age.